PENERAPAN UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERIKANAN TERHADAP PENYELUNDUPAN BIBIT LOBSTER DI PENGADILAN NEGERI TEMBILAHAN - Erwin, Risto; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The background of this research is that based on the decision of the Tembilahan District District Court judges against the perpetrators of criminal acts smuggling lobster seeds is not effective because the impact caused by the crime of smuggling lobster seeds is not comparable with the sentence given in accordance with article 88 of Law Number 45 of 2009 concerning amendments to Law Number 31 of 2004 concerning Fisheries, which is based on stating that everyone who with intentionally entering, issuing, procuring, distributing, and or maintaining fish that is detrimental to the community, fish cultivation, fish resources, and or environmental fish resources into and or out of the territory of the Republic of Indonesia fisheries management as referred to in article 16 paragraph (1), sentenced to a maximum imprisonment of 6 (six) years and a maximum fine of Rp. 1,500,000,000.00 (one billion five hundred million rupiah) but the judge only imposed the law of the defendant in prison for 1 (one) year and 8 (eight) months and a fine of Rp. 1,000,000,000.00 (one billion rupiah) provided that if the Defendant does not pay the fine, then it will be replaced with imprisonment for 3 (three) months. The purpose of this writing, namely; First, to find out the application of excuses for smuggling lobster seeds in the Tembilahan District Court, Second, to find out the reason for the judge to decide on the application of criminal sanctions against smuggling lobster seeds in the Tembilahan District Court.This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conducted research at the place of study in order to provide a complete and clear picture of the problem under study, this research was conducted at Tembilahan District Court, while the population and sample were all parties relating to the problems examined in this study.From the results of the study that the application of the Law Nom to smuggling lobster seeds in the Tembilahan District Court that is ineffective and not in accordance with legal provisions where the act is very detrimental to the State and has the effect of damaging the natural ecosystem and contrary to article 88 of Law Number 45 of 2009 Regarding changes to Law Number 31 of 2004 concerning Fisheries.Keywords: Application - Smuggling - Lobster Seeds